Stigma and Quality of Life in Women With Breast Cancer: Mediation and Moderation Model of Social Support, Sense of Coherence, and Coping Strategies - Zamanian, Hadi; Amini-Tehrani, Mohammadali; Jalali, Zahra; Daryaafzoon, Mona; Ramezani, Fatemeh; Malek, Negin; Adabimohazab, Maede; Hozouri, Roghayeh; Rafiei Taghanaky, Fereshteh (Frontiers in Psychology, 2022)
Objectives The breast cancer stigma affects Health-related quality of life (HRQoL), while general resilience resources (GRRs), namely, sense of coherence (SOC), social support, and coping skills, are thought to alleviate this effect. The study aimed to explore the mediating/moderation role of GRRs in the relationship between stigma and HRQoL and its dimensions in Iranian patients with breast cancer. Methods In this cross-sectional study, Stigma Scale for Chronic Illness 8-item version (SSCI-8), SOC-13, Medical Outcome Survey- Social Support Scale (MOS-SSS), Brief COPE, and Functional Assessment of Cancer Therapy-Breast (FACT-B) were investigated in a convenience sample of Iranian women with confirmed non-metastatic breast cancer. Following the establishment of correlations using Pearson’s correlation, single and parallel mediation analysis and moderation analysis were conducted to determine the extent to which each GRR might be impacted by stigma or decrease the adverse impact of stigma on HRQoL. Results An analysis of 221 women (response rate of 87.5%) with the mean age of 47.14 (9.13) showed that stigma was negatively correlated to all HRQoL’s dimensions (r = −0.27∼0.51, p < 0.05), SOC (r = −0.26∼0.35, p < 0.01), social support (r = −0.23∼0.30, p < 0.01), and the bulk of coping skills. In the single mediation analysis, stigma affected all facets of SOC, all subscales of social support, and positive reframing, which partially reduced breast cancer HRQoL. Stigma affects general HRQoL through damaging meaningfulness, social support (except for tangible), and positive reframing. Meaningfulness was marked as the most impacted GRR in terms of all domains of HRQoL. In parallel mediation, reduced meaningfulness, total social support, and positive reframing were highlighted as the pathways of diminished breast cancer HRQoL. Moderation analysis indicated the higher levels of humor, behavioral disengagement, and use of instrumental support behaviors to be functional in protecting different dimensions of HRQoL, while the results were mixed for venting, especially in patients with mastectomy surgery. Conclusion While GRRs may be impacted by stigma, they exert a relatively small protective effect against the impact of stigma on HRQoL. This study provides some novel findings, but longitudinal studies are needed to further verify these before any causal conclusion or recommendations for health policy can be drawn.